Challenge and strategies of nurses at the neonatal intensive care unit - Sandra Neves de Melo Cardoso; Cínthia Maria Gomes Escoto Esteche; Márcia Maria Coelho Oliveira; Maria do Socorro Mendonça Sherlock; Maria Vera Lúcia Moreira Leitão Cardoso (Rev Rene)
The assistance services to newborns need to be structured and organized, and nurses’ participation must be essential for the care practice. We aimed, with this study to describe the main challenges and strategies of nurses that work at a neonatal intensive care unit (NICU). This is a descriptive exploratory study with quantitative approach carried out in Fortaleza-CE-Brazil. 24 nurses of three reference hospitals were interviewed, using a questionnaire with open and closed questions, from May to June 2008. Regarding the difficulties in assistance, we could highlight: lack of material, 15 (34.0%); inappropriate material, 8 (18.1%); low qualification of professionals, 7 (15.9%); and overcrowded/beds 5 (11.3%). As for the strategies: answers to scientific and technological knowledge, 12 (35.2%); and humanized assistance, 9 (26.4%). We believe that the constant updating implicates in the improvement of care and performance of professionals optimizing their practice. We may conclude that a guided and qualified caregiver is fundamental, for neonatal assistance.